Study of a biperiodic slow-wave structure at medium energies - Zagorodnov, O.G.; Papkovich, V.G.; Khizhnyak, N.A. (Вопросы атомной науки и техники, 1999)
In the present work charged particle accelerators occupy the important place both in scientific, and in practical applications.